2021
DOI: 10.18502/aoh.v5i4.7970
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Study Based on PMV-PPD in the Building of a Screening Center for COVID-19

Abstract: Background: One way to achieve a standard heating, ventilating, and air conditioning system with maximum satisfaction is to use a thermal index to identify and determine the thermal comfort of people. In this study we intend to evaluate thermal comfort based on PMV-PPD (Predicted Mean Vote/Predicted Percentage Dissatisfied) model in workers of screening center for COVID-19. Methods: The study period was from March 1 to October 31, 2020. In this study, we used the ISO 7730 model to determinate PMV-PPD ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results showed that operable windows could significantly impact indoor air quality, health, safety, and student performance. Mohammadi and Nasrabadi (2021) showed the thermal comfort conditions from March to October in the hot and arid climate of Birjand. According to the results, October was the only month when the thermal comfort conditions were met.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that operable windows could significantly impact indoor air quality, health, safety, and student performance. Mohammadi and Nasrabadi (2021) showed the thermal comfort conditions from March to October in the hot and arid climate of Birjand. According to the results, October was the only month when the thermal comfort conditions were met.…”
Section: Introductionmentioning
confidence: 99%